ገበታ: የአየር ለውጥን መቋቋም ስለሚችሉ የተሻሻሉ የእንስሳት መኖ ቴክኖሎጂዎች የራዲዮ ፕሮግራም፡ ክፍል አራት - International Livestock Research Institute (International Livestock Research Institute, 2025)
The fourth broadcast from Debre Birhan on Fana FM 90.0 focused on fodder beet and its benefits for dairy production. Farmers from North Shewa shared how it has helped improve their milk production. A livestock expert also described its characteristics and how it supports livestock feeding. This radio program series is produced by the CGIAR Sustainable Farming and Scaling for Impact (S4I) programs and Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA), and the Technologies for African Agricultural Transformation (TAAT) projects.